Interaksi Genotipe x Lingkungan pada Morfologi Malai Galur-galur Padi (Oryza sativa L.) Bermalai Lebat - Jayaningsih, Elvita Dwi; Suwarno, Willy Bayuardi; Nindita, Anggi; Aswidinnoor, Hajrial (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Breeding rice for heavy panicle is prospective to improve production. However, the information on genotype x environment interaction (GxE) of rice panicle morphology is limited. This study was aimed to evaluate the GxE interaction on panicle morphology of heavy panicle rice (Oryza sativa L.) genotypes. The experiments were conducted in four environmental conditions. The research was conducted from December 2017 to May 2019 at the Department of Agronomy and Horticulture, IPB University, using 24 genotypes (F5-F6 generation) with 6 check varieties. The experimental design was an augmented design (3 replicates of check). Analysis of variance showed that GxE interaction effects were significant on the panicle length, number of axis nodes, primary branches number, secondary branches number, tertiary branches number, number of grains per panicle, and grain density per primary branch. The results showed that the two environments in the rainy season produced higher primary branches number, secondary branches number, tertiary branches number, number of grain per panicle, and grain density per primary branch than the two environments in the dry season. Correlation and path analyses showed that panicle length, number of secondary branches, and grain density per primary branch had a significant and direct positive effect on the number of grains per panicle. Keywords: primary branches, panicle length, secondary branches, tertiary branches